Performance Evaluation and Adsorption Isotherm of Activated Bottom Ash for Free Fatty Acid Removal - Ardiansyah, Novellia; Utami, Anggia Afza; Amir, Amelia; Ulfah, Maria (Universitas Nusa Bangsa, 2025)
Boiler bottom ash is one of the by-products produced from the combustion of palm shells and fiber in the boiler furnace at high temperature. These were usually disposed of on the land around the palm mill, causing environmental problems. In this research, non-activated and activated bottom ash treated with phosphoric acid were used as an adsorbent for removing free fatty acids (FFA) from crude palm oil (CPO) recovery. This study had two parameters. The first parameter is an adsorbent activator concentration with the variation level of 0, 5, 10, and 15 %. The second parameter is contact time with four levels involved in this research. They were 1, 2, 3, and 4 hours. The bottom ash adsorbent with a 10% concentration of phosphoric acid and a 3-hour contact time had the highest efficiency and capacity in removing FFAs from CPO recovery. The lowering of water and impurity content in CPO recovery after the adsorption process was in the range of 0.05% to 0.22% and 0.01% to 0.04%, respectively. The isotherm model was evaluated using the Langmuir and the Freundlich. The Isotherm model was fitted to the Freundlich, and this indicated multilayer adsorption with R2 = 0.9869.